Analisis Peran Perempuan Pesisir dalam Usaha Ekonomi Produktif Rumah Tangga di Kelurahan Cambaya Kota Makassar - Jusnawati Jusnawati; Bahrul Amsal (Jurnal Commercium: Kajian Masyarakat Kontemporer, 2019)
The role of women in general can be categorized into two namely domestic roles and public roles. Both roles with different domains are also carried out by coastal women in the Cambaya sub-distric of Makassar.This study aims to identify the forms of productive economic activities of coastal women and the role of coastal women in the productive economic activities of households in the Cambaya urban village of Makassar. The research method used is a qualitative method with observational data collection techniques without participation, in-depth interviews, documentation, audio and visual material.The research informant was taken through a purposive sampling method with the characteristics of women as fishermen’s wives, having children, owning independent businesses. The research data were analyzed using componential analysis techniques. The results showed that the forms of coastal women’s businesses in the productive economy of households can be categorized into2 types of businesses namely; 1) trade category, namely selling fish caught by fishermen, selling various basic needs and snacks and opening a food stall at home or around the house, 2) Production category, is the effort to manage the catches to manage the catches to become salted fish and ebi. The role of coastal women in the productive economy of their households in line with form of business undertaken, where coastal women play a dual role, namely by carrying out their domestic and public role. The public role performed by coastal women is not only limited to the management of independent businesses or concerns their performance in certain institutions, but is related to the formation of networks and other social activities that can support the productive economic activities of their households.